Neoadjuvant chemoimmunotherapy as a potential therapeutic option in NSCLC UICC stage IIIA with multilevel N2 disease. (2022) - Menghesha, Hruy; Doerr, Fabian; Schlachtenberger, Georg; Estremadoyro, Andres Amorin; Töpelt, Karin; Wahlers, Thorsten; Hekmat, Khosro; Heldwein, Matthias
Abstract: Lung Cancer is still one of the leading causes for cancer related death worldwide. The determination of an adequate therapeutic approach requests a precise staging, which contains computed tomography (CT) of the thorax, positron emission tomography computed tomography (PET-CT), cerebral magnetic resonance imaging (cMRI) and pulmonary function testing as well as the patient's opinion. In UICC stages I and II, if there is functional operability and technical resectability, the treatment of choice is primary surgery followed by adjuvant therapy depending on lymph node status, while patients in the metastatic stage IV, or with locally advanced, nonresectable disease are more likely to receive definitive chemoradiation therapy. The UICC Stage III (8th edition) combines a heterogeneous group of patients that remains the focus of discussion regarding the optimal therapeutic regimen, which ranges from primary surgical care to a neoadjuvant therapeutic approach, to definitive conservative treatment. Since March 2020, we have been treating a patient on an interdisciplinary basis who initially had a UICC stage IIIA multilevel N2 pulmonary adenocarcinoma and finally underwent successful surgery after a very good response to neoadjuvant chemoimmunotherapy. Our latest follow-up showed no evidence of recurrence. Similar to current ongoing studies our case shows, that neoadjuvant immunotherapy is a reasonable alternative to conventional neoadjuvant chemotherapy.